Towards an information provision strategy for university libraries in Ghana - Edwin Ellis Badu; Brendan Loughridge (Information Research: An International Electronic Journal)
This article describes on-going research on the development of a library strategy for universities in Ghana. The research focuses on the factors affecting the development of a strategic planning process aimed at improving the libraries' capacity to deliver information services effectively and efficiently. Since the structure of universities in Ghana is, to a great extent, derived from or modelled on that of universities in the United Kingdom the project of necessity also includes some consideration of current attitudes to the strategic planning process in a number of university libraries in the United Kingdom. It is hoped that the study and evaluation of this aspect of the management of United Kingdom university libraries may provide pertinent guidelines for university library management in Ghana.